USP9X stabilizes XIAP to regulate mitotic cell death and chemoresistance in aggressive B‐cell lymphoma - Engel, Katharina; Rudelius, Martina; Slawska, Jolanta; Jacobs, Laura; Ahangarian Abhari, Behnaz; Altmann, Bettina; Kurutz, Julia; Rathakrishnan, Abirami; Fernández‐Sáiz, Vanesa; Brunner, Andrä; Targosz, Bianca‐Sabrina; Loewecke, Felicia; et al. (EMBO molecular medicine, 2016)
The mitotic spindle assembly checkpoint (SAC) maintains genome stability and marks an important target for antineoplastic therapies. However, it has remained unclear how cells execute cell fate decisions under conditions of SAC‐induced mitotic arrest. Here, we identify USP9X as the mitotic deubiquitinase of the X‐linked inhibitor of apoptosis protein (XIAP) and demonstrate that deubiquitylation and stabilization of XIAP by USP9X lead to increased resistance toward mitotic spindle poisons. We find that primary human aggressive B‐cell lymphoma samples exhibit high USP9X expression that correlate with XIAP overexpression. We show that high USP9X/XIAP expression is associated with shorter event‐free survival in patients treated with spindle poison‐containing chemotherapy. Accordingly, aggressive B‐cell lymphoma lines with USP9X and associated XIAP overexpression exhibit increased chemoresistance, reversed by specific inhibition of either USP9X or XIAP. Moreover, knockdown of USP9X or XIAP significantly delays lymphoma development and increases sensitivity to spindle poisons in a murine Eμ‐Myc lymphoma model. Together, we specify the USP9X–XIAP axis as a regulator of the mitotic cell fate decision and propose that USP9X and XIAP are potential prognostic biomarkers and therapeutic targets in aggressive B‐cell lymphoma. Synopsis USP9X deubiquitylates and stabilizes anti‐apoptotic protein XIAP and promotes mitotic survival. Overexpression of USP9X/XIAP confers chemotherapy resistance and associates with decreased survival in aggressive B‐cell lymphoma patients. USP9X deubiquitylates and stabilizes XIAP in mitosis The USP9X‐XIAP pathway promotes mitotic survival USP9X and XIAP are overexpressed in Diffuse Large B Cell Lymphoma (DLBCL) The USP9X‐XIAP axis promotes lymphoma growth and resistance to spindle poisons Overexpression of USP9X and XIAP associates with chemotherapy resistance in DLBCL patients Graphical Abstract USP9X deubiquitylates and stabilizes anti‐apoptotic protein XIAP and promotes mitotic survival. Overexpression of USP9X/XIAP confers chemotherapy resistance and associates with decreased survival in aggressive B‐cell lymphoma patients.